A NOTE ON NON-FRAGMENTABLE SUBSPACE OF \(_ ꝏ^c\)(Γ) - Heydari, F.; Behmardi, D. (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper we consider \(_ ꝏ^c\)(Γ) where Γ is uncountable and introduce subspaces \(A_P\)\(_P ∈ Σ\) of \(_ ꝏ^c\)(Γ) which are fragmented by a metric that generates the discrete topology but A = \(_P ∈ Σ\) A\(_P\) is not countable unions of fragmentable subspaces.